Can ultrasound measurement of bladder wall thickness be a useful adjunct for regular urodynamics in children with spina bifida?. Issue 5 (October 2021) - Togo, Mio; Kitta, Takeya; Chiba, Hiroki; Ouchi, Mifuka; Abe-Takahashi, Yui; Higuchi, Madoka; Kusakabe, Naohisa; Shinohara, Nobuo
Summary: Introduction: Spina bifida is a major cause of neurologic bladder dysfunction among children. The goal of neurogenic bladder treatment is to preserve renal function. Close follow-up is essential, as lower urinary tract functions can change with patient growth. Presently, invasive urodynamics is the gold standard for precisely assessing lower urinary tract function. Ultrasound is a low-cost, non-invasive, uncomplicated examination that can be easily repeated. Bladder wall thickness (BWT) measurement by ultrasound has been proposed as a non-invasive alternative for identifying lower urinary tract dysfunctions. Objective: Currently there are few reports on BWT in children with spina bifida, and BWT assessment methodology has yet to be defined. The present study aim was to investigate whether BWT could be a useful adjunct for regular urodynamics in children with spina bifida. We especially focused on the precise bladder volume during BWT measurements that were simultaneously performed with urodynamics. Study design: This prospective observational study investigated 33 patients with spina bifida who underwent video urodynamics. We assessed BWT measurements using ultrasound simultaneously performed with video urodynamics. BWT was calculated for the ventral and dorsal walls at 0%, 20%, 40%, 60%, 80%, and 100% of the expected bladder capacity. Results: Median of bladder capacity was 240 mL, and bladder compliance was 19.2 mL/cmH2 O. Detrusor overactivity was present in 66.7% and vesicoureteral reflux was present in 27.3% of the patients. BWT of the ventral wall was significantly lower than the dorsal wall. During increases in the bladder volume, both the ventral and dorsal walls exhibited proportional thinning (p < 0.05). There were no significant differences for BWT between males and females. Although there was a higher statistical tendency for detrusor overactivity versus without detrusor overactivity (p = 0.085), there were no significant differences found between patients with and without detrusor overactivity. Discussion: This is the first report where multiple BWT measurements points with video urodynamics were simultaneously performed. Selection of bladder volumes for BWT measurements is critical. Our current study measured six points for each patient during urodynamics. However, available data was not sufficient for detecting bladder function. Until now, there has been no valid standard condition defined for measuring BWT and thus, lack of a standardized method has resulted in discrepancies among studies. Conclusion: Our measurement conditions showed BWT may not correlate with the degree of bladder detrusor dysfunction. As BWT ultrasound cannot identify bladder dysfunction of children with spina bifida, this cannot be used as a substitute for invasive urodynamics. Summary Table Methodologies across studies. Table References Year Number of patients Subject of study Ultrasound Measurement Bladder volume at Measurement BWT (mm) Correlation Müller et al. 2000 150 Healthy subject Ventral + dorsal BWT Not defined Ventral: 0.9 (0.4–2.9) Dorsal: 1.1 (0.4–2.8) Müller et al. 2006 66 MMC Ventral + dorsal BWT Before catheterization Ventral: 0.8 (0.3–2.1) No correlation Tanaka et al. 2008 57 MMC Dorsal BWT Not defined 3.9 ± 1.0 (unfavorable) 2.4 ± 0.7 (favorable) MDP, DLPP, DO Sekerci et al. 2014 80 MMC Ventral + dorsal BWT MCC 4.0 (2.5–6.1) DLPP, renal scarring Kim et al. 2015 53 MMC Ventral BWT 25％, 50%, 100% MCC 1.6 ± 0.4 (100%) 2.0 ± 0.5 (50%) 2.6 ± 0.7 (25%) Trabeculation Tiago et al. 2018 63 MMC Dorsal BWT MCC 3.8 (3.1–4.8) DO Current study 33 MMC Ventral + dorsal BWT 0%, 20%, 40%, 60%, 80%, and 100% of EBC Ventral 20%: 1.42 ± 0.41 Dorsal 20%:1.62 ± 0.46 No correlation BWT: bladder wall thickness, MMC: myelomeningocele, MCC: maximum cystometric capacity, DO: detrusor overactivity, MDP: Maximum detrusor pressure during filling or at leak, DLPP: Detrusor leak point pressure, EBC: Expected bladder capacity.